If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+2(a+3)=3(2a-1)+6
We move all terms to the left:
1+2(a+3)-(3(2a-1)+6)=0
We multiply parentheses
2a-(3(2a-1)+6)+6+1=0
We calculate terms in parentheses: -(3(2a-1)+6), so:We add all the numbers together, and all the variables
3(2a-1)+6
We multiply parentheses
6a-3+6
We add all the numbers together, and all the variables
6a+3
Back to the equation:
-(6a+3)
2a-(6a+3)+7=0
We get rid of parentheses
2a-6a-3+7=0
We add all the numbers together, and all the variables
-4a+4=0
We move all terms containing a to the left, all other terms to the right
-4a=-4
a=-4/-4
a=1
| x-0.12x=224 | | -4+2y=-6 | | 9x2-31x+25=0 | | 1024=640(1+.15x) | | 2x/x-3+2/x=3 | | X-0.08x=368 | | 5/3x2-x=1/3 | | 25+2x=10+5x | | -34(-41)=x/9 | | 3+4c=48 | | 3/y+2+5/y-6=8/y+3 | | 2+2x=3(2x+2)-5(x-3) | | 2x^2+25x-7.9=0 | | x+3/4+x+3/5=2 | | -4=6v | | 48-(5x-7=-8 | | 120p=180 | | 7(x+7)+2=7x+2 | | 0.11=0.000000175v+0.5(7.18*10^12)(0.000000175)^2 | | 7=05d | | 0.5y+1.5=0.6y-2.4 | | 166=102-v | | 12-12y+2y=7 | | 1/3v+2v+v=180 | | n=2222+9 | | 300=7.5r | | 0.9(4x+7)=3.4-(x-3) | | 1.5t=30.0 | | 27-11=4(x-2) | | 10-5/6x=-15 | | 8x+4=2(x-6) | | 63=28y |